2019
DOI: 10.1186/s12913-018-3861-8
|View full text |Cite
|
Sign up to set email alerts
|

Burden of community-acquired pneumonia, predisposing factors and health-care related costs in patients with cancer

Abstract: BackgroundData on the burden of community-acquired pneumonia (CAP) and health-care related costs in patients with cancer is scarce. We aimed to estimate the CAP incidence rate, mortality, and healthcare-related costs of CAP patients with different cancer subtypes in Germany.MethodsWe used German health claims data of a representative sample of 4 million subjects to conduct cohort studies in patients with a new diagnosis of lung, hematological, breast, gastro-intestinal tract and renal/urinary-tract cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
1
20
2
Order By: Relevance
“…This study was conducted based on the InGef (former HRI) database with anonymized data from approximately 6.7 million individuals in Germany insured in one of approximately 70 German statutory health insurance providers (SHIs) currently contributing data to this database (mainly company or guild health insurances) [ 4 , 16 ]. For this study, a representative sample of the German SHI population regarding age and sex (approximately five percent of the German population) was created.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted based on the InGef (former HRI) database with anonymized data from approximately 6.7 million individuals in Germany insured in one of approximately 70 German statutory health insurance providers (SHIs) currently contributing data to this database (mainly company or guild health insurances) [ 4 , 16 ]. For this study, a representative sample of the German SHI population regarding age and sex (approximately five percent of the German population) was created.…”
Section: Methodsmentioning
confidence: 99%
“…database (mainly company or guild health insurances) [4,16]. For this study, a representative sample of the German SHI population regarding age and sex (approximately five percent of the German population) was created.…”
Section: Plos Onementioning
confidence: 99%
“…This is of particular concern with regard to S. pneumoniae as pneumonia is the most common serious infection found in patients with cancer. 48,49 Further, human infections by S. pneumoniae serotypes 19F, 11A, and 9N, the 3 serotypes with the most significant radiation-induced deficiencies in IgG response, have each been associated with increased mortality. 50 Collectively, the study reported here adds to the growing body of mouse, NHP, and human data indicating that in addition to the dramatic acute effect of radiation exposure, TBI leads to subtle long-term immunologic defects.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Known or potential risk factors for CAP were included in logistic regression to calculate the propensity score. The risk factors included age, 8 10 Chinese ethnicity, male gender, 11 smoking status, 9 drinking status, 11 history of psoriasis, history of IBD, use of sulfasalazine, etanercept, infliximab, adalimumab, golimumab, certolizumab, secukinumab, use of steroids for more than ½ year, diabetes, 12 chronic renal impairment, 12 malignancy, 13 , 14 chronic lung disease, 15 chronic heart disease, 12 other immunosuppressants or immune-suppressed states, 11 and cerebrovascular accident. 12 The score was grouped into pentiles with non-overlapping parts trimmed.…”
Section: Methodsmentioning
confidence: 99%